Effect of seed storage and light conditions on the growth rate of Crescentia alata (Bignoniaceae) - Valverde-Rodríguez, Kimberly (2019)
The dry tropical forest tree Crescentia alata is a cultural and economical resource, but efforts to establish plantations, which could satisfy commercial production and avoid impact on natural populations, have been unsuccessful. So there is a need to generate biological information on this species for obtaining plants in greenhouses. The aim of this work was to evaluate the vigor and growth rate of C. alata seedlings born from seeds that were stored at different periods and temperatures, and to determine the effect of light intensity on the seedlings. Fruits were collected in Liberia (Guanacaste, Costa Rica) and seeds stored for 0, 4, 8, and 14 months at 5 °C, 15 °C, and ambient temperature (22-24 °C). Seedlings from seeds stored for 0, 4, 8 and 14 months were grown to evaluate growth after 8 days, 2 months, and 16 months, and in two different light conditions. Morphology of 8-day-seedlings changed according to storage time. Principal component analysis of 2-month evaluation indicates that the most significant variables were total dry biomass, dry biomass of leaves, root-shoot, stem, and root, while for the analysis of 16-month evaluation these variables were dry biomass of root, root-shoot, and leaves, also leaf number, and shoot length. Specific leaf area of 16-month plants from seeds stored for 14 months did not change with storage temperature. In addition, two different light conditions influence seedling height, stem diameter or leaf number. Seed storage at 5 °C and 15 °C favored development of seedling cotyledons, and length of both root and hypocotyl. Two month-seedlings from 0M and 8M allocated most biomass to roots and less to stems, enhancing this way water absorption. Sixteen-month-plants from non-stored seeds developed the highest leaf numbers, and those plants from 8M seeds at 5 °C and 15 °C showed shorter stems. Seeds stored up to 14 months kept viable, becoming healthy seedlings. We recommend that future researchers evaluate seed viability at different drying temperatures and more contrasting light levels.